Minimizing human race creating an unknown climate leading to pandemics-Need of the time - K Suresh (Annals of Environmental Science and Toxicology - Peertechz Publications, 2022)
We are on a planet that orbits the Sun which emits a huge amount of energy. The climate we experience is a result of an energy gradient across Earth and an imbalance in energy across the world due to axial tilt of Earth rotation.